4(1-3x)=2(-4x+7)

Simple and best practice solution for 4(1-3x)=2(-4x+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(1-3x)=2(-4x+7) equation:



4(1-3x)=2(-4x+7)
We move all terms to the left:
4(1-3x)-(2(-4x+7))=0
We add all the numbers together, and all the variables
4(-3x+1)-(2(-4x+7))=0
We multiply parentheses
-12x-(2(-4x+7))+4=0
We calculate terms in parentheses: -(2(-4x+7)), so:
2(-4x+7)
We multiply parentheses
-8x+14
Back to the equation:
-(-8x+14)
We get rid of parentheses
-12x+8x-14+4=0
We add all the numbers together, and all the variables
-4x-10=0
We move all terms containing x to the left, all other terms to the right
-4x=10
x=10/-4
x=-2+1/2

See similar equations:

| 4z+12+-14=26 | | 2u–6=5u-78 | | 5u–78=2u–6 | | 3v+81=15v+9 | | 4z+12+-14=26z=2 | | 2x-5=44=5x | | 3w+3w+3w+24=78 | | f+6=-11 | | 12(2s+5)=108 | | f6=-11 | | X^2-2x/(x-1)^2=0 | | 13x+21=10x | | -78=6s | | 12x+1516=-40-16x | | 2x^2+3x^2=140 | | h(7)=0.8(3/5)^7 | | 2(7p+3)=-22 | | 4x-3x+24=-14 | | 8x-12=84 | | r(7)=(11/12)^7 | | 4x−3(x−8)=−14 | | 42=h-32 | | –64=–16+–3d | | d=284−−−√3 | | g(7)=360(0.45)^7 | | 5x+27=3280 | | (5x+10)+90+135=360 | | y=725(1-0.1)^7 | | 3(2p+1)=-21 | | (5x+10)+90-270=360 | | 73.4=b/7 | | 4x/x+5=×/x+4 |

Equations solver categories